Comparison of a geometric-based and an evolutionary technique for tracking storm systems - Parikh, Jo Ann; DaPonte, John S.; Vitale, Joseph N.; Tselioudis, George (Applications and Science of Computational Intelligence III, 2000)
The objective of this study is to compare geometric-based and evolutionary techniques for tracking storm systems from sequences of satellite images. Analysis was applied to the International Satellite Cloud Climatology Project low resolution D1 database for selected storm systems during the month of September, 1988. During this time period there were two exceptionally long tracks of major hurricane systems, Hurricanes Gilbert and Helene. Cloud top pressure and cloud optical thickness were used to identify storm systems. The ability of the geometric-based and evolutionary techniques to generate tracks through storm regions was assessed. Differences in final tracking results between the two techniques resulted not only from the differences in methodology but also form differences in the type of preprocessed input used by each of the techniques. Tracking results were compared to results disseminated by the Colorado State/Tropical Prediction Center and maintained by the National Hurricane Center in Miami, Florida. For the hurricanes investigated in this study, both techniques were able to generate tracks which followed either most or some of the portions of the hurricanes. The evolutionary algorithm was in general able to maintain good continuity along the tracks but, with no knowledge of overall region movement, was unable to discern which of two possible directions would be best to pursue in cases where there were tow or more equally close storm systems components. The geometric method was able to maintain a smooth track close to the course of the hurricane except for confusion primarily at the beginning and/or end of tracks.
Keywords: Algorithms; Computational geometry; Database systems; Evolutionary computation; Image analysis; Satellite image processing; Satellites; Storm tracking; Storms; dept.csc

Switching theory approach to alarm correlation in network management - Aboelela, E; Douligeris, Christos (IEEE, 2000)
Several working or experimental management systems use expert systems techniques for fault management purposes. Although the effort in the area is still growing, most of the expert fault management systems developed were built in an ad-hoc and unstructured basis simply transferring the knowledge of the human expert into an automated system. However, to meet future challenges, a theoretical foundation for fault management must be established aiming to bridge the gap between the working systems and research, and to provide a general structured model easily expandable to future networks. In this paper an algorithm is proposed to simplify the set of clustered alarms. This algorithm is based on the techniques widely used in the Logic Design field to simplify switching functions. The performance of the proposed algorithm is analyzed and the results are compared to those of a traditional algorithm.
Keywords: Alarm correlations; Algorithms; Correlation theory; Expert systems; Network management; Switching theory; Telecommunication networks; dept.csc

Field-by-field evaluation of intraoperative transoesophageal echocardiography interpretative skills - Griffin, Michael J; Edwards, Bruce; Judd, Jon; Workman, Robert; Rafferty, T (Physiological Measurement, 2000)
A quality assurance system is essential for the credibility and structured growth of anaesthesiology-based transoesophageal echocardiography (TEE) programmes. We have developed software (Q/A Kappa), involving a 400- line source code, capable of directly reporting kappa correlation coefficient values, using external reviewer interpretations as the 'gold standard', and thereby allowing systematic assessment of the validity of intraoperative echocardiographic interpretation. This paper presents assessment of the validity of 240 intraoperative anaesthesiologists' echocardiographic interpretations, and, in addition, the results of field testing of this prototypical software. Data, derived from consecutive cardiac surgery patients, consisted of standardized two-dimensional transoesophageal echocardiographic, colour flow and Doppler imaging sequences. Intraoperative and off-line 'gold standard' TEE interpretations were compared for 19 fields or variables using the Q/A Kappa program. The kappa correlation coefficients were highly variable and dependent on the examination field, ranging from 0.08 for apical regional wall motion scores to 1.00 for tricuspid regurgitation grade, left atrial measurement, aortic valve anatomy and left ventricular long axis and short axis global function. The correlation coefficients were also operator dependent. These data (480 interpretations) were also manually integrated into the equation required for calculation of values of the variable kappa correlation coefficient. The relationship between Q/A Kappa-derived values and manually calculated values was highly significant (p < 0.001; r = 1.0). The implications and possible explanations of the results for particular examination fields are discussed. This study also demonstrates successful seamless functioning of this software program from data entry, segmentation into tables and valid statistical analysis. These findings suggest that it is practical to provide sophisticated continuous quality improvement TEE data on a routine basis.
Keywords: Cardiovascular surgery; Coefficient values; Correlation coefficient; Echocardiography; Field-by-field evaluation; Gold standards; Intra-operative; Intraoperative; Kappa correlation; Line sources; Quality assurance; Quality assurance systems; Quality control; Software testing; Source codes; Transesophageal echocardiographies; Transoesophageal echocardiography; article; competence; controlled study; correlation function; dept.csc; heart surgery; human; intraoperative period; major clinical study; priority journal; quality control; transesophageal echocardiography